Effect of Organizational Communication, Leadership Communication, and Work Discipline on Occupational Health and Safety at PT Armada Bangun Samudra (PT ABS) - Hanifah Handayani; Kholil Kholil; Dewi Widiowati (Syntax Corporation Indonesia, 2022)
Communication is something that is required in everyday life to express thoughts or ideas to invite others to act and produce desired changes, both in terms of individuals and organizations. Within organizations, communication has an impact on organizational performance. This study aims to determine the effective communication model of OHS in PT Armada Bangun Samudra (PTABS), a shipbuilding company. Data were collected from 185 respondents who were selected randomly from a pool of 344. Data analysis used Structural Equation Modeling (SEM). The results reveal that communication can be effective in an organization with multiple sub-organizations/sections if it is carried out in a hierarchical manner one level above or below. This study found that the leader’s communication skills had a significant effect on work discipline. Employee work discipline has a significant effect on the company’s OHS performance. To improve OHS performance, organizational leaders' communication skills and employee participation at all levels must be improved.